Den unge Grundtvig som kultur psykolog. Om "Europa, Frankrig og Napoleon" - Michelsen, William (Grundtvig-studier, 1955)
The Young Grundtvig as a Culture Psyckologist. On “ Europa, Frankrig og Napoleon” ( “ Europe, France and Napoleon9). By William Michelsen. An essential part of Grundtvig’s strong influence in Denmark is due to his writings and speeches in the eigteen-thirties, -forties and -fifties about national education (»folkeopdragelse«) and national character. As during these years he was trying to adopt his mode of expression to suit his readers and his hearers, it is perhaps not so very remarkable that it is difficult to find any order and inner connection in this confused mass of ideas. However, if one follows them back to his first published writings, it becomes clear that there lies not only definite view of history (the Biblical view), but also a definite psyckological outwork, behind Grundtvig’s descriptions of the characteristics of different nations and behind his interpretation of contemporary events. This can be seen partly in some drafts, dating from 1813, for a series of lecture entitled » Om Menneskets Vilkaar« (“ Of Human Circumstance”), and partly in his three » Verdenskrøniker« (“ World Chronicles”), especially the second one, dating from 1814, of which only one volume was published, and, finally, in a characteristic essay published in 1815 with the tittle » Europa, Frankrig og Napoleon« (“ Europe, France and Napoleon”). The book was written under the emotional impact of the dreaded General’s return from Elba, but was not published till after his depart at Waterloo, and, probably for that reason, has been but little known. Grundtvig sees Napoleon’s victorious advance as a link in the chain of attempts to win the lordship of the world which are known to history, and seeks in his book to explain the motives behind every attempt to dominate man. not only politically, but also culturally — in other words: behind every spiritual tyranny. Feeling, according to Grundtvig, is the faculty from which the other mental faculties have developed. He considers that there is a parallel between the “outer” (physical) senses: sight, touch &. hearing, and the “inner” (psychic) senses: the faculty of imagination, feeling and reason. The whole mass consists not only of mind and body, but also of spirit, since he is created as a “shadowy likeness” of the triune God. The Fall, according to Grundtvig, has not annihilated but only effaced this order. And the confusion of tongues at the Tower of Babel has indeed caused men to forget their original basic language, but the different peoples have nevertheless preserved those elements of the basic language which they loved. Their languages are thus an expression of the interests of the different peoples, and thereby of their character. Grundtvig therefore speaks of the Semites as “the people of fantasy”, whose interest is especially in the unseen world, of the Egyptians and the Romans as the people of intellect or reason, specially interested in material things, and of the other Indo-european peoples as “the people of the heart”, each with its “language of the heart”, determined by the feelings which they have specially developed. But since the nationalities have become intermixed, Grundtvig prefers in “ Europa, Frankrig og Napoleon” to characterise them in accordance with the stage they have reached in the development of the feelings, especially the ambition to dominate others. Mans desire to rule the world agrees in and for itself with God’s plan; he was created to be God’s vice-regent on earth. But as soon as he seeks to make himself independent of God, he enters the service of the Devil. From this point of view Grundtvig judges all human efforts, and claimes that this judgment is confirmed by history: “ No one in Christendom has been able to win any lasting influence without the help of religion”, he says. The power of the Popes stood and fell according as they were regarded as vice-regents og Christ on earth; and the (German) Holy Roman Emperor was enable to take over their dominion when the Reformantion broke out in the northern part of Europe. The striwing for independence in more recent times shows itself especially in a one-sided developement of reason without sufficient regard for the more primitive mental faculties, the faculty of imagination and feeling. Grundtvig claims indeed, as early as 1815, that “the strength of reason rests upon the depth of the preceding feeling”, and that “one can never come to comprehend what one has not loved, because comprehension is only the revelation of feeling”. The climax of reason’s striwing for independence has been reached, according to Grundtvig, in the French Revolution and the natural philosophy of the German Romantic School; a combination of these two powers would therefore be the most dangerous enemy of Christianity. Grundtvig sees the decisive sign that the Devil is playing his tricks in the fact that the champions of the independence of reason must demand to dominate the reason of their opponents. But yet it should have the same right to independence! Therefore, according to Grundtvig, it is a self-contradiction to want to make reason an absolute sovereign in the life of the mind. The characteristics which must be developed in a people to enable it to attain the empire of the world are, according to Grundtvig, first strength, then sublimity, next to this purity, and lastly clarity. Grundtvig in 1815 finds the same fault in the Greeks as he found, in “ Nordens Mytologi” (“ The Mythology of the North”) in 1832, in the humanists of modern times; they were impatient & wanted to begin with clarity. The Romans on the other hand had strength, but lacked purity, &. the peoples that were subjugated by the Romans — especially including the French — are, according to Grundtvig, infected by the impure heart of the Romans. The pure heart must therefore be found in a people who have never been subjugated by the Romans, and Grundtvig finds it in the Danes. Grundtvig considers that the Germans are characterised by their zeal and capacity for “purefying” everything, only excepting their own heart. Luther is the great exception. In the rationalist Bible criticism and in the critical filosophy of Kant and his successors, Grundtvig sees the combination of pride and desire for purification which is characteristic of the Germans; they want to make themselves judges of the touchstone itself and purify God’s Word. When Grundtvig calls the natural philosophy of the Romantic School “the Devil’s masterpiece”, he means that it is the most cunning attempt he knows to construct a philosophy of life which makes Christianity superfluous. In his discussion of Schellings philosophy it can be seen that Grundtvig conceived of a twofold development of the life of the mind, partly a fleshly or sensuous one and partly a spiritual one. In &. for itself he can well conceive of the life of the mind as developed from the fleshly or sensuous element in man, but in that case he lacks an explanation of its conceptions of God &. an unseen spiritual world. Since man has in fact such conceptions, Grundtvig finds a natural explanation of this in the Bible story of God’s having breathed into man something of His own life — spirit. He conceives that the presupposition for the active operation of the spiritual “inner senses” is that they have first — passively and involuntarily (i. e., without any intention of doing so) — received the image of things which cannot be seen with outer sense of sight. It is these images which awaken man’s spiritual feeling, and man becomes consious of this feeling with the help of spiritual reason. It is this that shows itself in the fact that man believes in the existence of these things which cannot be apprehended by the outer senses. Afterwards the faculty of imagination can then voluntarily (i. e., with the intention of doing so) recreate these images and thus awaken anew the spiritual feeling and the spiritual reason. The Fall of man which Grundtvig attacks in his own period consists, therefore, in the fact that the spiritual reason in its arrogance confounds the spiritual feeling in man with the superhuman power which first produced the images in the mind of man. It pretends that man himself had created these images &. thereby the whole of man’s spiritual life. It oversteps its natural boundaries and sets man in the place of God.